Gut feelings : the intelligence of the unconscious - Gigerenzer, Gerd. (New York : Viking, 2007)
Gigerenzer is one of the researchers of behavioral intuition responsible for the science behind Malcolm Gladwell's bestseller Blink. Gladwell showed how snap decisions often yield better results than careful analysis. Now, Gigerenzer explains why intuition is such a powerful decision-making tool. Drawing on a decade of research, Gigerenzer demonstrates that gut feelings are actually the result of unconscious mental processes--processes that apply rules of thumb that we've derived from our environment and prior experiences. The value of these rules lies precisely in their difference from rational analysis--they take into account only the most useful bits of information rather than attempting to evaluate all possible factors. By examining various decisions we make, Gigerenzer shows how gut feelings not only lead to good practical decisions, but also underlie the moral choices that make our society function.--From publisher description.
Incluye referencias bibliográficas (p. [251]-269) e índice.
Keywords: Racionalidad